The Study of Assessment in the Merdeka Curriculum at Elementary School - Dea Amelia; Ina Mutmainah; Intan Indriyani; Nathaline Sesaria Carmenette (Universitas Pendidikan Indonesia (UPI), 2023)
Assessment is very needed in learning. Assessment in the educational context is defined as a series of activities that include collecting, analyzing and interpreting data to determine the level of understanding and performance of students during the learning process. Without conducting an assessment, it is impossible for us to verify that the goals and objectives have been achieved. Each curriculum that is carried out by the Ministry of Education and Culture of the Republic of Indonesia must have an assessment to assess students' abilities or achievements in their learning activities; the same goes for the Merdeka Curriculum. Therefore, this article aims to provide information and discuss assessment studies in the Merdeka Curriculum in elementary schools. This research is included in the category of qualitative research with library research methods by collecting and evaluating data from library sources that are relevant to the research topic. This research refers to books, articles, journals, and other appropriate sources. Based on research results from several journals, it is proven that by conducting assessment studies, student learning outcomes will reflect their respective competencies. The conclusions based on the results of the literature review carried out are that assessment is very important in the application of learning, especially in the Merdeka Curriculum. There are many examples in the Merdeka Curriculum, such as diagnostic assessments, summative assessments, and also formative assessments, all of which are equally useful for knowing the value or quality of students' absorbing the learning that has been given by the teacher to them.